Concussions in Sledding Sports and the Unrecognized “Sled Head”: A Systematic Review - McCradden, Melissa D.; Cusimano, Michael D. (Frontiers in Neurology, 2018)
BACKGROUND: Sport-related concussion is a significant public health concern. Little research has been conducted on sport-related concussion and injury prevention strategies in competitive sledding sports like bobsleigh, luge, and skeleton. Athletes have identified ‘sled head’ as a key concern due to its symptom burden. PURPOSE: To summarize our knowledge of the prevalence of concussion and related symptoms in sledding sports; to utilize Haddon's Matrix to inform and define strategies for injury prevention. METHODS: An independent information specialist conducted a search for the known literature on injuries in non-recreational sledding sports, and specifically for concussion via OVID Medline, CINAHL, the Cochrane Database, EMBASE, PsycInfo, PubMed, Scopus, and the Web of Sciences from 1946 to December 2017. After iterative searches of reference sections, a total of 844 articles were assessed for inclusion. RESULTS: Nine articles were included for review. Concussions are a common occurrence in elite sledding sport athletes, affecting 13-18% of all sledding athletes. Significant variance exists between events, indicating a potential effect of the ice track in injury risk. The condition known as ‘sled head’ is discussed and identified as a key point of further investigation. A number of potential injury prevention strategies are discussed. INTERPRETATION: Head injuries and concussions are an important injury for elite sledding sports and a number of avenues exist for prevention. More work is required to delineate the mechanisms, characteristics, natural history and management of ‘sled head’.